Design and performance testing of a monolithic nickel-based SiC catalyst for steam methane reforming - Shen, Ziqi; Nabavi, Seyed Ali; Clough, Peter T. (Elsevier, 2024)
Hydrogen is a highly promoted carbon-free energy carrier that has drawn significant attention recently due to its potential to decarbonise energy sector. More than three-quarters of hydrogen is currently produced via steam methane reforming (SMR), and nickel-based catalysts are used in most applications. Structured catalysts have been reported to be able to further improve catalyst performance as they can optimise heat and mass transfer, as well as prevent coke formation with its structural and textural proprieties. Silicon carbide (SiC) has excellent hardness, thermal conductivity, and chemical inertness, therefore is a promising material to develop structured nickel-based monolithic SiC catalysts for SMR. In this work, a structured monolithic catalyst support has been formed by a modified freeze-gelation method, initially starting from SiC powder, and nickel has been distributed to form a monolithic nickel-based catalyst by wet impregnation. The results showed that the catalysts can achieve thermodynamic equilibrium at 600 °C with a gas hourly space velocity (GHSV) of 10,000 h−1, while reaching a high methane conversion of 86% at 800 °C and GHSV value of 20,000 h−1 during the performance tests using low feeding concentration and low pressure. This is the first time SiC catalytic materials have had their performance demonstrated for SMR under realistic operating conditions.
Keywords: Structured catalysts; Silicon carbide; Monolith; Steam methane reforming; Hydrogen production